TEACHING AUXILIARY VERBS IN ENGLISH LANGUAGE EDUCATION: A COMPREHENSIVE APPROACH - Berdiyeva Zamona (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
This article explores the critical role of auxiliary verbs in English grammar, emphasizing their importance for constructing various verb tenses, moods, and voices. It examines different types of auxiliary verbs, including modal auxiliaries and primary auxiliaries, as well as their specific functions in English syntax. The paper delves into practical teaching strategies and techniques, focusing on overcoming the challenges that learners often face. This includes using contextualized examples, interactive activities, and technological tools. The article underscores the necessity of a clear and systematic approach to auxiliary verb instruction to foster effective language learning and fluent communication.